Translation: A Key Component of a Hundred-Year Project - Samphel, Tsondue; Namgyal, Dadul; Drongbu, Dawa Tsering; Khangsar, Karma Tenzin (Frontiers in Communication, 2021)
ABSTRACT The Emory-Tibet Science Initiative (ETSI) has embarked on a historic endeavor of introducing a systematic and sustainable science education program within the traditional Tibetan monastic institutions. His Holiness the Dalai Lama, who conceived and supports this initiative, calls it a hundred-year project. From the beginning, translation has been an integral part of this project because of the need to prepare course materials as well as to facilitate on-site classes and lab activities through translation to the Tibetan language. The translation process involves not just conveying novel and foreign concepts across cultures but doing so often with an English scientific language peppered with unfamiliar terms that require Tibetan translations that often have been coined in an ad hoc manner. In addition to the linguistic barriers, cultural and technical ones further complicate the process of communication. A case in point is the concept of life, or correlation versus causation, or the view that consciousness is an emergent property of brain, where each construct has its corresponding but differing concept in Tibetan Buddhism. When engaging with such existing parallel yet divergent terms or concepts, the translators must strike a delicate balance and avoid forsaking the distinctive characteristics and connotations involved. In this report, the ETSI translation team share their journey—highlighting the needs felt, challenges faced, and solutions sought. We discuss the translation principles guiding our work and the handling of such scientific features as acronyms, units, chemical names, and formulas. We also reflect on the work accomplished and our future plans.